Identification, cloning and functional characterization of novel beta-defensins in the rat (Rattus norvegicus) - French Frank S; Radhakrishnan Yashwanth; Wingard Christopher J; Chintalgattu Vishnu; Yenugu Suresh; Hall Susan H (BMC, 2006)
Abstract Background beta-defensins are small cationic peptides that exhibit broad spectrum antimicrobial properties. The majority of beta-defensins identified in humans are predominantly expressed in the male reproductive tract and have roles in non-immunological processes such as sperm maturation and capacitation. Characterization of novel defensins in the male reproductive tract can lead to increased understanding of their dual roles in immunity and sperm maturation. Methods In silico rat genomic analyses were used to identify novel beta-defensins related to human defensins 118-123. RNAs isolated from male reproductive tract tissues of rat were reverse transcribed and PCR amplified using gene specific primers for defensins. PCR products were sequenced to confirm their identity. RT-PCR analysis was performed to analyze the tissue distribution, developmental expression and androgen regulation of these defensins. Recombinant defensins were tested against E. coli in a colony forming unit assay to analyze their antimicrobial activities. Results Novel beta-defensins, Defb21, Defb24, Defb27, Defb30 and Defb36 were identified in the rat male reproductive tract. Defb30 and Defb36 were the most restricted in expression, whereas the others were expressed in a variety of tissues including the female reproductive tract. Early onset of defensin expression was observed in the epididymides of 10-60 day old rats. Defb21-Defb36 expression in castrated rats was down regulated and maintained at normal levels in testosterone supplemented animals. DEFB24 and DEFB30 proteins showed potent dose and time dependent antibacterial activity. Conclusion Rat Defb21, Defb24, Defb27, Defb30 and Defb36 are abundantly expressed in the male reproductive tract where they most likely protect against microbial invasion. They are developmentally regulated and androgen is required for full expression in the adult epididymis.